Metal hydride actuator for a rescue jack driven by hydrogen desorption. (8th November 2019) - Hosono, Minako; Sakaki, Kouji; Nakamura, Yumiko; Ino, Shuichi
Abstract: This paper presents a metal hydride (MH) actuator rescue jack that uses hydrogen-absorbing alloy as its pressure source. The MH actuator is attached to a thin and flexible fiber-reinforced rubber bag end effector, enabling it to pry open narrow and rough gaps. The proposed MH rescue jack was prepared with different amounts of alloy (6–15 g). The results showed that, with only 6 g of alloy, the rescue jack was able to jack up a 100 kg weight to a height of 10 mm within 1 min by heating the alloy container to 50 °C. Moreover, the jack-up speed increased as the amount of alloy increased. A mathematical model was derived from the jack-up operation tests to estimate the jack-up height, with the aim of designing appropriate amounts of hydrogen-absorbing alloys for rescue jack development. According to the experimental results, the response of the jack-up height was modeled as a first order system in time domain. The model was defined as a function of alloy amount, and its validity was assessed by comparing the experimental and simulation results. The results were in good agreement which confirmed the potential of the proposed model as a design tool for jacks from the viewpoint of time constant. Highlights: Metal hydride (MH) actuator for a rescue jack is developed. MH actuator using only 6 g of alloy can jack up 100 kg by 10 mm within 1 min. Jack-up speed is increased as the amount of hydrogen-absorbing alloy increases. Mathematical model for the performance of the MH actuator rescue jack is determined. Proposed model can predict the appropriate amount of hydrogen-absorbing alloy.